ALMOND (Amygdalus communis) IN TNE SOUTH OF KYRGYZSNAN (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
This article presents the results of many years of research into introduced varieties of sweet almonds. The recommended varieties of sweet almonds for industrial plantings are paper-shell, soft-shell and standard-shell varieties.
Keywords: Almond, kernel, variety strength, shell character, color, natural conditions